Human Relations In Socio-Cultural Based Educational Organizations In High - Rusdiman AB; Osberth Sinaga; Wanafri Pangaribuan; Zainuddin (CV. AFDIFAL MAJU BERKAH, 2023)
The school as an organization certainly has an organizational culture that plays an important role in realizing the school's vision and mission. School organizational culture is the norms adopted and implemented by all components of the school to achieve the vision and mission of the school effectively. This study aims to describe the school organizational culture at SMK Negeri 1 Bireuen in preparing superior human resources and school programs to support school culture. The method used in this observation is a qualitative approach with data collection techniques through observation, interviews, and documentation. The subjects of the study included elements of school residents, namely vice principals, teachers, and students. The results of this observation show that (1) SMK Negeri 1 Bireuen has three excellent cultures, namely a culture of discipline, cooperation, and industrial work culture, (2) there are several supporting programs for students in the application of school culture, (3) there are supporting factors and obstacles to the realization of an effective school organizational culture. According to the observations, the school organizational culture at SMK Negeri 1 Bireuen can already be said to be effective.